ANALYSIS OF DETERMINANTS OF MIGRATION OUTFLOW OF HIGHLY QUALIFIED SPECIALISTS FROM THE REPUBLIC OF UZBEKISTAN AND DEVELOPMENT OF STRATEGIES FOR THEIR RETENTION IN THE NATIONAL ECONOMY (Marketing Journal, 2025)
This article examines the pressing issue of highly qualified specialist migration in modern Uzbekistan, known as "brain drain." Based on an analysis of statistical data and the legal framework, key factors driving the emigration of the intellectual elite are identified. These are dominated by economic (income level), professional (career and scientific prospects), and socio -living (living conditions) reasons. The article proposes a set of strategies and specific measures for talent retention, including improving state policy, creating a favorable environment for research and development, and fostering public -private partnerships in science and innovation. The study shows that effectively countering "brain drain" requires a systemic approach, combining short -term incentives with long-term investments in human capital and institutional reforms.
Keywords: causes of migration; economic factors; career prospects; scientific infrastructure; recipient countries; state policy; innovation potential; system analysis; development strategies; reintegration